2010
DOI: 10.1021/ac100359p
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Improvements in Peptide Recovery at Elevated Chromatographic Temperatures from Microcapillary Liquid Chromatography−Mass Spectrometry Analyses of Brain Using Selected Reaction Monitoring

Abstract: Elevated chromatographic temperatures are well recognized to provide beneficial analytical effects. Previously, we demonstrated that elevated chromatographic temperature enhances the identification of hydrophobic peptides prepared from enriched membrane samples. Here, we quantitatively assess and compare the recovery of peptide analytes from both simple and complex tryptic peptide matrices using the SRM mass spectrometry. Our study demonstrates that elevated chromatographic temperature results in significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
(31 reference statements)
1
21
1
Order By: Relevance
“…These results indicated that C8 stationary phase was of high efficiency for the analysis of hydrophobic peptides from IMP digests, which might be attributed to the different retention capability of C8 and C18 stationary phases for hydrophobic peptides. For C18, the hydrophobic peptides were strongly retained, tending to lower hydrophobic peptide recovery, which was in accordance with previous study by Wu et al [30][31][32].…”
Section: Comparison Of C18 and C8 On Imp Digest Separationsupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicated that C8 stationary phase was of high efficiency for the analysis of hydrophobic peptides from IMP digests, which might be attributed to the different retention capability of C8 and C18 stationary phases for hydrophobic peptides. For C18, the hydrophobic peptides were strongly retained, tending to lower hydrophobic peptide recovery, which was in accordance with previous study by Wu et al [30][31][32].…”
Section: Comparison Of C18 and C8 On Imp Digest Separationsupporting
confidence: 92%
“…Therefore, the conventional C18 stationary phase may reduce the recovery of hydrophobic peptides due to its long alkyl chain, which further affected the MS identification capability. To solve this problem, Wu et al applied RPLC at elevated temperature prior to identification by electrospray ionization tandem mass spectrometry (ESI-MS/MS) [30], to reduce the retention of hydrophobic peptides and increase their recovery [31,32]. However, for this strategy, an additional device for adjusting the column temperature and heat-stable packing materials are indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…Practical aspects of using elevated temperatures Sample recovery considerations Better recovery and increased solubility of hydrophobic peptides and proteins at elevated temperature has been previously demonstrated [59]. Several reports indicated the impact of elevated temperature on peptide secondary structures including the dissociation of dimers and unfolding of amphipathic helical peptides [60].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated temperature dramatically increases the rate of cis-trans isomer interconversion of the imido peptide bond that results in elution of a Pro-containing peptide in a single symmetrical sharp peak [61]. Such an improvement may noticeably enhance overall sensitivity of proteomic profiling and quantitative characterization using LC-MS-based techniques because the frequency of proline occurrence is relatively high (e.g., 6.4 % and 6.23 %, top 6th amino acid in Homo sapiens and Mus musculus, accordingly [59]). Due to the lower retention of peptides at high temperatures in reversed phases, the maximum percent of organic modifier in the mobile phase can be significantly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Peptides were eluted from the column at a constant flow rate of 200 nl/min using a linear 90 min gradient of 3-33% B (A = 98% water/2% ACN/0.1% formic acid; B = 99.9% ACN/0.1% formic acid). The column was heated at 40 °C to enhance the detection of hydrophobic peptides [42,43]. MS1 spectra were collected from m/z 400-1400 at a resolving power of 60,000 at 400 m/z , and precursor ion counts of 1,000,000 were acquired with a maximum injection time of 200 ms.…”
Section: Methodsmentioning
confidence: 99%